"The peer workers, they get it" – how lived experience expertise strengthens therapeutic alliances and alcohol and other drug treatment-seeking in the hospital setting. (4th March 2023) - Francia, Leanne; Berg, Amelia; Lam, Tina; Morgan, Kirsty; Nielsen, Suzanne
Abstract: Introduction and aims: Despite a long history of the adoption of a peer workforce in alcohol and other drug treatment service provision, there is limited peer reviewed literature on the benefits of peer worker role integration in the hospital setting. Our qualitative study explored the perceptions of people with lived experience of problematic alcohol and other drugs use and their experiences of peer worker roles in the hospital setting. Design and methods: Twenty semi-structured interviews with people who experienced problematic alcohol and other drug use. Transcripts were thematically analyzed and guided by a broad interest in a therapeutic alliance. Results: We identified four themes related to how lived experience expertise within a peer worker role strengthened therapeutic alliances: (i) by building trust and credibility; (i) by building hope; (iii) the ability to approach informally; and (iv) in continuing to be accessible long term. Discussion and conclusion: The results partly echo earlier literature, however highlight two innovative aspects that relate to lived experience expertise that maintain therapeutic alliances in the hospital setting being, firstly, the ability to approach informally, and secondly, an opportunity for longer-term engagement. In Australia at present there is a window of opportunity to better integrate peer workers into clinical care models, and as such our results have implications for how policy makers might better approach peer worker integration and configuration to improve treatment-seeking intentions both within and beyond the hospital setting.